Calreticulin Release at an Early Stage of Death Modulates the Clearance by Macrophages of Apoptotic Cells - Osman, Rim; Tacnet-Delorme, Pascale; Kleman, Jean-Philippe; Millet, Arnaud; Frachet, Philippe (Frontiers in Immunology, 2017)
Calreticulin (CRT) is a well-known “eat-me” signal harbored by dying cells participating in their recognition by phagocytes. CRT is also recognized to deeply impact the immune response to altered self-cells. In this study we focus on the role of the newly exposure of CRT following cell death induction. We show that if CRT increases at the outer face of the plasma membrane and is well recognized by C1q even when phosphatidylserine is not yet detected, CRT is also released in the surrounding milieu and is able to interact with phagocytes. We observed that exogenous CRT is endocytosed by THP1 macrophages through macropinocytosis and that internalization is associated with a particular phenotype characterized by an increase of cell spreading and migration, an up regulation of CD14, an increase of IL8 release and a decrease of early apoptotic cell uptake. Importantly, CRT-induced pro-inflammatory phenotype was confirmed on human monocytes-derived macrophages by the over expression of CD40 and CD274 and we found that monocytes-derived macrophages exposed to CRT display a peculiar polarization notably associated with a down regulation of the histocompatibility complex of class II molecules hampering its description through the classical M1/M2 dichotomy. Altogether our results highlight the role of soluble CRT with strong possible consequences on the macrophage-mediated immune response to dying cell.